"All is Normal": Sports Mega Events, Favela Territory, and the Afterlives of Public Security Interventions in Rio de Janeiro. (16th August 2021) - Oosterbaan, Martijn
Abstract: This article discusses the changes in Visionário, a favela located near the affluent neighborhoods in Rio de Janeiro, to assess the effects of the Sports Mega Events (SMEs) on the political and economic conditions in the favela. Following Harvey's (2005) description of "accumulation by dispossession, " several authors have highlighted that the UPP policing program, implemented before the SMEs, was part of neoliberal efforts to colonize favela territory with the prospect of future gain. Visionário has witnessed two consecutive policing programs (GPAE and UPP) in the past twenty years. Both were aimed at disarming the drugs‐gang members who attempt to rule the favela by force. The ethnography in this article shows that both policing programs started ambitiously, yet gradually police officers withdrew and gang members reoccupied strategic positions in the favela. As a result, residents learnt to deal with ongoing territorial shifts in a highly dense urban space and with the liminal presence of police officers. In my analysis, I argue that in terms of neoliberal strategies to accumulate favela territory by dispossession, this case suggests a failure, and I analyze the struggle over favela territory as the outcome of contradictory forces connected to global neoliberalization.